Towards Establishing Principles for Designing Cybersecurity Simulations of Cyber-Physical Artefacts in Real-Time Simulation - Dang, Duong; Vartiainen, Tero; Mekkanen, Mike (Universitat Politècnica de València, 2021)
Our modern world is dependent on cyber-physical artefacts (e.g., smart grids, cars, mobile phones). Those artefacts are being attacked by cyber-criminals entailing substantial harm to individuals, organizations, and governments. Those artefacts need to be designed properly to prevent and recover from inevitable cyberattacks. We offer a solution based on a RealTime Simulator (RTS). Our solution is meta-principles for using RTS when designing simulations in Cyber-Physical artefacts. Our solution considers both social and technical layers of cyber-physical artefacts.
Keywords: Cyber Physical Security; design science; Principles; Real-time Simulator; fi=Tietotekniikka|en=Computer Science|